Comparación in vitro del grado de adaptación de cofias coladas unitarias de cromo níquel antes y después de la aplicación de la cerámica - Riega Huatuco, Juan Carlos (2014)
The purpose of this in vitro study was to compare the adaptation of the cast copings marginal unitary nickel chromium before and after application of the ceramic. The investigation was experimental in vitro. Thirty-two lower premolars were divide in two groups. One group was conducted by the Laboratory Oral Lab S.C.R.L. and the other by Surgical Medical Services VADI S.A.C. The copings and veneering were made following each laboratory standards. The marginal adaptation was measured by a Steromicroscope (Leica Microsystems LAS EZ version 2.0.0, Switzerland) in microns in four zones (mesial, distal, lingual and buccal) before and after application of ceramic. The better marginal adaptation was obtained in group 1A (cap before application of ceramic) with an average of 54.97 μm, while a smaller average marginal adaptation was register in group 1B (cap after application of ceramic) with a mean of 69.08 μm. No statistically significant differences were found when comparing the adaptation before and after application of ceramic (p=0.569) and when comparing both laboratories (p=0.851). Lower marginal mismatch was found in group 2B (cap after application of ceramic). It was concluded that the application of ceramic improved the marginal adaptation, however it has to take into account different parameters such as the manufacture of each laboratory, cooking time, etc. There was significant difference in marginal adaptation comparing the two laboratories.